Development of Global Ethics Through Pancasila Student Profile at RA Perwanida 1 Palangka Raya - Hilmatunnisa, Hilmatunnisa; Sidqi, Nasiruddin (AS-SABIQUN, 2024)
The development of science and technology in dealing with it requires a person or several people who have extraordinary morals, abilities and qualifications. Education is a strategic basis in the current era of globalization. The purpose of this research is that researchers want to know how the development of global ethics through the profile of Pancasila students. In accordance with the characteristics of the problems raised in this research, a qualitative research method is used, namely emphasizing its analysis on descriptive data in the form of written words that are observed. Data collection techniques are by using observation and documentation. The results of this study are that the development of global ethics has been integrated through a project to strengthen the profile of Pancasila students at RA Perwanida 1, the project is carried out once in one semester. Apart from that, the theme raised also adapts to the characteristics of the school and its students. The importance of developing global ethics is not only seen in the classroom, but also through various extracurricular activities and social interactions between students and teachers. Thus, the development of global ethics in schools forms not only morally good individuals, but also individuals who are ready to participate in building a peaceful and harmonious global society. In this context, the implementation of global ethics in educational institutions, such as that carried out by RA Perwanida 1 through the independent curriculum.